Studi Literatur Kualitas Audit Kantor Akuntan Publik Dalam Perspektif Homo Islamicus - Julfan Saputra; Saparuddin Siregar (ITB AAS INDONESIA Surakarta, 2022)
This study reviews the literature related to the analysis of the audit quality of public accounting firms in the perspective of Homo Islamicus. This study aims to analyze the role of audit quality in moderating the effects of principal-principal agency conflict and to analyze auditor competence and independence on audit quality. This type of research is descriptive qualitative research with a literature study approach that comes from books, literature, and library materials related to the purpose of this research. This literature research was conducted during the 2015-2020 period on 44 published fulltext literature. The results of this study indicate that in relation to the audit quality of public accounting firms in a homo Islamic perspective, it shows that auditors from different countries tend to have different attitudes and cultures, such as incentives, perceptions, and behaviors of auditors, clients, and users of financial statements in different countries. there is a difference. This shows that the reports presented are more varied over time. In addition, this study finds that there is some evidence of a relationship between individualism and litigation, and the auditor's consideration of doing additional audit work.